Do chronic heart failure symptoms interact with burden of treatment? Qualitative literature systematic review. Issue 7 (30th July 2021) - Austin, Rosalynn C; Schoonhoven, Lisette; Clancy, Mike; Richardson, Alison; Kalra, Paul R; May, Carl R
Abstract : Objective: Explore the interaction between patient experienced symptoms and burden of treatment (BoT) theory in chronic heart failure (CHF). BoT explains how dynamic patient workload (self-care) and their capacity (elements influencing capability), impacts on patients' experience of illness. Design: Review of qualitative research studies. Data sources: CINAHL, EMBASE, MEDLINE, PsycINFO, Scopus and Web of Science were searched between January 2007 and 2020. Eligibility Criteria: Journal articles in English, reporting qualitative studies on lived experience of CHF. Results: 35 articles identified related to the lived experience of 720 patients with CHF. Symptoms with physical and emotional characteristics were identified with breathlessness, weakness, despair and anxiety most prevalent. Identifying symptoms' interaction with BoT framework identified three themes: (1) Symptoms appear to infrequently drive patients to engage in self-care (9.2% of codes), (2) symptoms appear to impede (70.5% of codes) and (3) symptoms form barriers to self-care engagement (20.3% of codes). Symptoms increase illness workload, making completing tasks more difficult; simultaneously, symptoms alter a patient's capacity, through a reduction in their individual capabilities and willingness to access external resources (ie, hospitals) often with devasting impact on patients' lives. Conclusions: Symptoms appear to be integral in the patient experience of CHF and BoT, predominately acting to impede patients' efforts to engage in self-care. Symptoms alter illness workload, increasing complexity and hardship. Patients' capacity is reduced by symptoms, in what they can do and their willingness to ask for help. Symptoms can lower their perceived self-value and roles within society. Symptoms appear to erode a patient's agency, decreasing self-value and generalised physical deconditioning leading to affective paralysis towards self-care regimens. Together describing a state of overwhelming BoT which is thought to be a contributor to poor engagement in self-care and may provide new insights into the perceived poor adherence to self-care in the CHF population. PROSPERO registration number: CRD42017077487.